Novel measures to assess the association of IPA agitation criteria domains with cognition, caregiver burden and quality of life in dementia. (31st December 2021) - Guan, Lily T; Sekhon, Ramnik; Kaur, Sharanjit; Chen, Hung‐Yu; K.V., Vineetha Warriyar; Burhan, Amer M.; Colman, Sarah; Derkach, Peter; Elmi, Sarah; Hussain, Maria; Krisman, Linda; Nair, Vasavan; et al.
Abstract: Background: Syndromic agitation as per International Psychogeriatric Association (IPA) criteria consists of three domains: verbal aggression (VA), physical aggression (PA), and excessive motor activity (EMA). The relationships between these domains and cognition, caregiver burden, and patient quality of life are not well established. We examined these associations utilizing data from a multisite clinical trial using novel measures for these domains. Method: Baseline participant data (n=128) from Standardizing Care for Neuropsychiatric Symptoms and Quality of Life in Dementia (StaN) study were utilized. Recently described IPA domain‐specific measures were implemented: domain prevalence was assessed with the NPI‐C‐IPA (derived from the Neuropsychiatric Inventory Clinician rating scale) and the CMAI‐IPA (derived from the Cohen Mansfield Agitation Inventory). Kendall's Tau‐B was utilized for correlations between agitation domains from both scales and the Montreal Cognitive Assessment (MoCA), Severe Cognitive Impairment Rating Scale (SCIRS), Zarit Burden Inventory (ZBI), and Alzheimer's Disease Related Quality of Life (ADRQL). Result: Using the NPI‐C‐IPA, 58.3% of participants had EMA, 58.3% VA, and 72.2% PA. With the CMAI‐IPA, 70.1% had EMA, 66.9% VA, and 45.2% PA. PA in both derived rating scales was correlated with poorer performance on the SCIRS (NPI‐C‐IPA: τb = ‐.21, p = .01, CMAI‐IPA: τb = ‐.29, p <.001). NPI‐C‐IPA EMA was correlated with poorer MoCA performance (τb = ‐.31, p =.01). Agitation in all three domains on the NPI‐C‐IPA was correlated with greater caregiver burden (EMA: τb =.16, p =.02, VA: τb =.14, p =.04, PA: τb =.15, p =.02), whereas only EMA was correlated with caregiver burden on the CMAI‐IPA (τb =.13, p =.04). Across both derived scales, the PA and VA domains were significantly correlated with poorer patient quality of life (NPI‐C‐IPA VA: τb = ‐.13, p =.04, NPI‐C‐IPA PA: τb = ‐.16, p =.01, CMAI‐IPA VA: τb = ‐.14, p =.03, CMAI‐IPA PA: τb = ‐.26, p <.001). Conclusion: The NPI‐C‐IPA and CMAI‐IPA both capture the IPA agitation domains, although differently. Domains measured with the NPI‐C‐IPA were more likely to correlate with the cognitive, caregiver burden, and quality of life outcomes compared to the CMAI‐IPA. Further research is required to determine the clinical significance of the differences in associations, and other salient domain‐specific features of the IPA agitation syndrome.